(untitled) (Bangladesh Journal of Microbiology, 2016)
Cellulase producing bacteria were isolated from cow dung and municipal solid wastes using enrichment technique. Cellulase activity was determined on carboxymethyl cellulose (CMC) agar medium supplemented with 1% CMC. Production of clear zones by the bacterial isolates on CMC agar was considered as indicative of extracellular cellulase activity. The greater size of transparent zone diameter was found proportional to the higher amount of cellulase production. Two bacterial isolates producing significant clear zone were identified as Pseudomonas spp based on morphological, cultural and biochemical characteristics. Fermentation was carried out under shake flask conditions for production of cellulase from Pseudomonas isolates in a basal medium containing CMC, KH2PO4, K2HPO4, MgSO4, NH4SO4, CaCl2 and FeSO4 at pH 7.0. The assay of cellulase viz. endoglucanase and exoglucanase in terms of CMCase and FPase, respectively was done by measuring the release of the reducing sugar. Some parameters influencing the production of cellulase by these bacterial isolates were investigated. Optimum level of cellulase was produced after 48 h of fermentation at 37°C with 5% inoculums size under continuous agitation at 120 rpm in the growth medium of pH 7.0. Optimum temperature and pH for the activity of cellulase from these bacterial isolates was 40°C and 7.0, respectively. Cellulase from these isolates was found almost stable at 25-40°C and pH 6.0-8.0 for 1 h. Furthermore, the cellulase activity was stimulated by Ca2+ and K+ but inhibited by Hg2+ and Zn2+, whereas, Mg2+ showed very low effect. Results reported herein indicated that the Pseudomonas isolates can be used as producer of extracellular cellulase. Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 11-16